THE PLC CONTROL OF AN ELECTRICAL SYSTEM CONSISTING OF AN ELECTROMAGNETICALLY SLIDING BRAKE AND COUPLING - Gabor, Georgel; Traian Plesca, Adrian (Journal of Energy Technology, 2024)
This paper describes an electrical system consisting of electrical sliding coupling driven by a 3 phase electric motor and electric sliding brake. A frequency converter provides control of the motor. Furthermore, the communication between PLC and frequency converter is done using PROFIBUS communication. The data are displayed on a SIEMENS HMI display. The goal is to control the electrical sliding coupling, which is mechanically connected to the electrical sliding brake.
Keywords: Electromagnetically sliding couple; lectromagnetically sliding brake; PLC; ROFIBUS; Variable Frequency Converter; Industrial communication